Evaluation of In-vitro Antioxidant Activity of Eclipta alba - Baldi, Dr.Ashish (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTAntioxidant potential of ethanolic extract of Eclipta alba was evaluated within the concentration range of 5-100 Âµg/ml using in-vitro studies viz. free radical scavenging capacity on 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical, 2,2-azinobis-(3-ethylbenzothiazoline-6-sulphonate) (ABTS) radical cation decolourization assay, scavenging of nitric oxide radical and total antioxidant capacity. Ascorbic acid was used as standard compound. Among antioxidant screening models tested, ethanolic extracts of E. alba had shown promising antioxidant potential in comparison to ascorbic acid. Therefore the results justify the free radical scavenging activity and therapeutic applications of E. alba in different systems of medicines.